2015
DOI: 10.1039/c5tc01544h
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and characterization of a new blue phosphorescent Ir complex

Abstract: As being incompatible with host materials in a physically blended emitting layer, phosphorescent dye is prone to form aggregation induced by Joule heat in devices under work. In this work, a new and efficient blue phosphorescent dye Cz-C8-FIrpic was designed and synthesised by incorporating 9-phenyl-9H-carbazole into a commonly used blue emissive iridium complex bis(4,6-(difluorophenyl)pyridine-N,C 2 ′)picolinate (FIrpic) via an alkyl chain linkage. This phosphorescent dye exhibits similar photophysical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…These isomers also exhibit similar maximum absorption peak and vertical excited energies of lowest singlet (S 1 ) and triplet (T 1 ) excited states. The calculated results also agree with the experimental data, 15 which demonstrated that the four isomers have similar optoelectronic properties.…”
Section: Resultssupporting
confidence: 80%
“…These isomers also exhibit similar maximum absorption peak and vertical excited energies of lowest singlet (S 1 ) and triplet (T 1 ) excited states. The calculated results also agree with the experimental data, 15 which demonstrated that the four isomers have similar optoelectronic properties.…”
Section: Resultssupporting
confidence: 80%
“…The radial distribution function (RDF) is a physical quantity that responds to the microstructure of a material and represents the ratio of the probability density of the occurrence of another atom or molecule at a distance around an atom or molecule to the probability density of a random distribution, solved by the equation: [ 39 ] gAB()rbadbreak=14πr20.28emt=1Kj=1NABnormalΔNAB()rr+δrNABK$$\begin{equation}{g_{AB}}\left( r \right) = \frac{1}{{4\pi {r^2}}}\;\frac{{\mathop \sum \nolimits_{t=1}^K \mathop \sum \nolimits_{j=1}^{{N_{AB}}} \Delta {N_{AB}}\left( {r \to r + \delta r} \right)}}{{{N_{AB}}K}}\end{equation}$$where 𝜌 𝐴𝐵 is the density of the system, 𝛿𝑟 is the distance difference, N AB is the number of atoms in the system A and B, Δ N AB is the number of atoms in the range r to r + 𝛿𝑟 where another atom appears, and K is the number of time steps.…”
Section: Resultsmentioning
confidence: 99%
“…As the ratio of the singlet and triplet excitons formed in OLED devices is 1:3, harvesting triplet excitons plays a very important role in improving device efficiency, such as for phosphorescent and TADF OLEDs. Therefore, ideal blue host materials should have not only a high Δ E g but also a high triplet energy ( E T ) to prevent the reversing of triplet excitons.…”
Section: Results and Discussionmentioning
confidence: 99%